Visibilizar a la mujer en tecnología: Estrategias de trabajo en la Ingeniería de Telecomunicación. - Barbancho-Pérez, Ana María; Barbancho-Pérez, Isabel; Tardón-García, Lorenzo José; Peinado-Domínguez, Alberto (IEEE, 2022)
Our society displays low representation of women in engineering and, in particular, in telecommunication engineering. This paper presents the different strategies that a group of professors at ETSI Telecommunication, Universidad de Málaga (UMA), have been carrying out since 2018 to make women visible in the technology framework: design of videos and posters about relevant women on the subjects, technological challenges to provide solutions to real problems regarding equality between men and women, women in engineering conferences, study of gender in students' work, etc.
Política de acceso abierto tomada de: https://conferences.ieeeauthorcenter.ieee.org/author-ethics/guidelines-and-policies/post-publication-policies/#accepted
Keywords: Mujeres en la ingeniería; Telecommunication; Engineering; Women; Equality; Visibility